Sulfur amino acid restriction, energy metabolism and obesity: a study protocol of an 8-week randomized controlled dietary intervention with whole foods and amino acid supplements - Stolt, Emma; Olsen, Thomas; Elshorbagy, Amany; Kožich, Viktor; van Greevenbroek, Marleen; Øvrebø, Bente; Thoresen, Magne; Refsum, Helga; Retterstøl, Kjetil; Vinknes, Kathrine J. (Journal of translational medicine, 2021)
Background Dietary sulfur amino acid (SAA) restriction is an established animal model for increasing lifespan and improving metabolic health. Data from human studies are limited. In the study outlined in this protocol, we will evaluate if dietary SAA restriction can reduce body weight and improve resting energy expenditure (REE) and parameters related to metabolic health. Method/design Men and women (calculated sample size = 60), aged 18–45 years, with body mass index of 27–35 kg/m 2 will be included in a double-blind 8-week dietary intervention study. The participants will be randomized in a 1:1 manner to a diet with either low or high SAA. Both groups will receive an equal base diet consisting of low-SAA plant-based whole foods and an amino acid supplement free of SAA. Contrasting SAA contents will be achieved using capsules with or without methionine and cysteine (SAA high , total diet SAA ~ 50–60 mg/kg body weight/day; SAA low , total diet SAA ~ 15–25 mg/kg body weight/day). The primary outcome is body weight change. Data and material collection will also include body composition (dual X-ray absorptiometry), resting energy expenditure (whole-room indirect calorimetry) and samples of blood, urine, feces and adipose tissue at baseline, at 4 weeks and at study completion. Measures will be taken to promote and monitor diet adherence. Data will be analyzed using linear mixed model regression to account for the repeated measures design and within-subject correlation. Discussion The strength of this study is the randomized double-blind design. A limitation is the restrictive nature of the diet which may lead to poor compliance. If this study reveals a beneficial effect of the SAA low diet on body composition and metabolic health, it opens up for new strategies for prevention and treatment of overweight, obesity and its associated disorders. Trial registration ClinicalTrials.gov: NCT04701346, Registration date: January 8th, 2021